Cross-cultural adaptation and validation of the Spanish sensory processing sensitivity questionnaire (S-SPSQ) - Salinas-Quintana, Pedro J.; Barría-Ramírez, Rodolfo; Acevedo, Bianca P.; Vega-Muñoz, Alejandro; Pérez-Chacón, Manuela; Chacón, Antonio (Frontiers in Psychology, 2024)
Sensory Processing Sensitivity (SPS) is a temperament trait rooted in biology, and is distinguished by heightened awareness, emotional responsiveness, and sensitivity to environmental stimuli. In this study, we aimed to enable the assessment of SPS within Spanish-speaking populations. To achieve this, we translated, adapted, and validated the Sensory Processing Sensitivity Questionnaire (SPSQ), which offers a comprehensive evaluation of SPS, encompassing both positive and negative aspects of the trait. Participants were 1,004 (844 females, mean age 37) mainly from Chile (964), and 40 were from other Spanish-speaking regions. Confirmatory factor analysis, utilizing the diagonally weighted least squares method, was applied to validate the internal structure of the Spanish version of the SPSQ (S-SPSQ). Fit indices such as GFI, CFI, TLI, RMSEA, and SRMR were scrutinized. Reliability assessment utilized Cronbach’s alpha and McDonald’s Omega. Three models were examined: Model I (six factors) displayed robustness, Model II (six factors plus a general factor) did not show substantive improvement, and Model III (Higher Order and Bifactor) excelled in fit while balancing complexity and representation, thus validating the findings of the original SPSQ and indicating similar reliability coefficients. The study offers a balanced perspective on SPS and contributes to cross-cultural validation of an SPS instrument which may facilitate research and guide personalized therapeutic interventions, thus enhancing outcomes for highly sensitive persons.